Peningkatan Literasi Menggunakan Teknologi Deep Learning Terhadap Guru TK dan SD di Pulau Tidung - Nugraha, Rana Gustian; Julia, J.; Iswara, Prana Dwija; Gusrayani, Diah; Panjaitan, Regina Lichteria (Universitas Pendidikan Nasional, 2025)
The problems in the world of education today show the importance of literacy that is not only limited to reading and writing, but also digital literacy and based on artificial intelligence (AI). However, there are significant challenges because many teachers are not yet good at interpreting this technology into learning. The purpose of the pinu research is to increase literacy with deep learning technology among teachers on Tidung Island. This study uses a seminar method of presentation techniques, independent assignments and peer tutors accompanied by the Pre-Test and Post-Test stages and a recapitulation of the results of various aspects of the activity. The results show a substantial increase in understanding and are evidenced by an increase in the average score of 32.1%. In addition, teachers realize that AI can accelerate the work of teacher needs. In conclusion, the method used can bridge the gap in access to technological information and successfully increase the capacity of human resources in the field of education. The implication is that this study emphasizes the need for ongoing efforts to improve teacher technology literacy for better professionalism.